2000
DOI: 10.1159/000008222
|View full text |Cite
|
Sign up to set email alerts
|

Remote Effects of Chronic Botulinum Toxin Treatment: Electrophysiologic Results Do Not Indicate Subclinical Remodelling of Noninjected Muscles

Abstract: This study investigates the remote effects of botulinum toxin injections by examining the motor unit architecture of noninjected distant muscles. In 21 dystonia patients treated with botulinum toxin (n = 11, mean cumulative dose = 815 mU; n = 10, mean cumulative dose = 7,207 mU) and 10 control individuals, a blinded single-fiber electromyography of the vastus lateralis muscle was performed. The main outcome measure was fiber density (FD), thus measuring the effect of different cumulative doses on remote reinne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Dutton 29 reported that patients receiving 200 units or more for torticollis have abnormal neuromuscular transmission in muscles as distant as the anterior tibialis muscle. However, Fertl et al 30 investigated the remote effects of botulinum toxin by examining the motor unit architecture of the vastus lateralis muscle. The electrophysiologic results did not indicate subclinical remodeling of noninjected muscles.…”
Section: Table 3 Changes In Amplitude and Area Of Compound Muscle Actmentioning
confidence: 99%
“…Dutton 29 reported that patients receiving 200 units or more for torticollis have abnormal neuromuscular transmission in muscles as distant as the anterior tibialis muscle. However, Fertl et al 30 investigated the remote effects of botulinum toxin by examining the motor unit architecture of the vastus lateralis muscle. The electrophysiologic results did not indicate subclinical remodeling of noninjected muscles.…”
Section: Table 3 Changes In Amplitude and Area Of Compound Muscle Actmentioning
confidence: 99%
“…15 Another study using single fibre EMG indicated that there was no evidence of remote re-innervation or subclinical remodelling of motor units in the vastus lateralis muscles of patients treated with btxA. 16 The methodological limitations of our study are those that are inherent to questionnaire/survey studies. Firstly, there could be sample selection bias, as the sample of physicians we surveyed was identified by their use of commercially available btxA, and perhaps some end users in a group practice were not identified to participate.…”
Section: Discussionmentioning
confidence: 83%
“…comm.]. In contrast, other studies demonstrate that there is no (distant) leg muscle atrophy [20] or subclinical muscle weakness [21]. In addition, it has been reported that BTX treatment in CD may even normalize the displaced topography of corticomotor projection of the (clinically non-dystonic) abductor pollicis brevis muscle [12].…”
Section: Discussionmentioning
confidence: 99%